Fluctuations of wind and temperature fields in Ninh Thuan - Binh Thuan waters and its possible relationship with coral bleaching - Chung, Tran Van; Tien, Ngo Manh; Nguyen, Cao Van (Vietnam Journal of Marine Science and Technology, 2021)
Temperature and wind on the sea surface are factors affecting the development of coral reefs in the seawaters. The research results show that the warming of sea water under the condition of weak wind field is considered a major threat to the bleaching of coral reefs in the sea areas of the Ninh Thuan - Binh Thuan provinces